THE GRAND SYNTAGMATIQUE OF POPULAR GENRE IN INDONESIAN CINEMA - Edoardo Irfan; Hermin Indah Wahyuni; Budi Irawanto (Taksasila Edukasi Insani, 2026)
This study examines the narrative structures of Indonesian popular films using Christian Metz’s Grand Syntagmatique framework. Three selected films—KKN di Desa Penari (2022), Dilan 1990 (2018), and Agak Laen (2024)—represent horror, romance, and comedy genres that achieved millions of admissions and reinforced the dominance of local cinema in the domestic market. The research employs structural textual analysis, consisting of segmentation, classification, and syntagmatic tabulation. Findings reveal that each genre strategically utilizes specific syntagmatic patterns: horror emphasizes suspense through alternation and bracket sequences, romance highlights intimacy via autonomous shots and ordinary sequences, while horror-comedy combines episodic and parallel sequences to generate humor and tension. These results demonstrate that the success of popular films relies not only on thematic resonance but also on the effectiveness of narrative structures in delivering accessible and engaging cinematic experiences. This study contributes to Indonesian film scholarship by underscoring the significance of formal analysis as a complement to thematic approaches, offering insights into how structural “grammars” shape audience appeal and genre conventions.Keywords: Christian Metz, Grand Syntagmatique, Genre, Indonesian popular cinema, narrative structure